Presentation of the Belarusian trading business on their own websites: advertising or self-assertion? - Mechkovskaya, Nina B. (Journal of the Belarusian State University. Philology, 2022)
Based on the investigation of the content structure of the websites of eight Belarusian trade enterprises, the place of the site in the aggregate information about the enterprise available in society is determined, and the communicative mechanisms of marketing management are characterised. It is shown that sites with information about the goods offered by the company do not represent a particularly effective sales engine, however, for a trading company and the business community as a whole, the site is important as evidence of the professional competencies of the company’s management in the field of commercial communication. Trading company websites perform three main functions. Firstly, they register customer discount cards (regular customers, members of the buyers’ club, etc.), thereby creating a customer database for targeted advertising and direct, or personal, sales. Secondly, sites organise databases about goods and services (of a given company), which allows, over time, to transform information and advertising sites into selling sites, i. e., into Internet commerce enterprises. Thirdly, a trading company’s own website is an important channel for its self-presentation and raising its status in the business community, since the communication quality of the website itself is a source of data that allows the business community to judge the level of professional competence of the company’s managers in the field of marketing communication and design.